Cold War Nature: Transforming German Poetry - Charlotte Melin (Studies in 20th & 21st Century Literature, 2018)
This essay considers German ‘Naturlyrik’ in terms of factors contributing to the mid-century emergence of political ecopoetry and 21st-century post-pastoral register. Cold War aesthetic experimentation connected with environmental concerns as poets, anthologists, and scholars bridged ideological differences by acknowledging shared values in relation to nature and environment. Material ecocriticism theory provides insight into how during the Cold War the lyric genre became the first to reclaim nature as a place of refuge, then protested the specter of an uninhabitable world, and eventually responded to humanly shaped nature. Work by poets Hans-Jürgen Heise, Peter Huchel, Wulf Kirsten, Ulrike Almut Sandig, and others is discussed.
Keywords: German poetry; nature; material ecocriticism; Cold War